Preparation of Pillar[5]arene‐Based [2]Rotaxanes from Acyl Chlorides and Amines (Eur. J. Org. Chem. 3/2015). Issue 3 (January 2015) - Milev, Radian; Lopez‐Pacheco, Alberto; Nierengarten, Iwona; Trinh, Thi Minh Nguyet; Holler, Michel; Deschenaux, Robert; Nierengarten, Jean‐François
Abstract : The cover picture shows a pseudorotaxane intermediate bearing an acyl chloride unit ready to react with an amine stopper to afford a pillar[5]arene‐based [2]rotaxane. The yield of [2]rotaxane is sensitive to the reaction conditions but also to electronic and structural factors, in particular the nature of the amine reagent and the size of the peripheral groups on both rims of the pillar[5]arene building block. Details are discussed in the article by R. Deschenaux, J.‐F. Nierengarten et al. on479 ff .